2005
DOI: 10.1080/02508281.2005.11081485
|View full text |Cite
|
Sign up to set email alerts
|

High Tech versus High Touch: Visitor Responses to the Use of Technology in Tourist Attractions

Abstract: There are a number of current debates in the academic and management literature about the benefits and costs of introducing technology into tourist experiences. The debate is an important one for those who manage tourist attractions when making decisions about which directions to take in the development of visitor experiences. A review of the relevant literature in tourism suggests that very little attention has been paid to tourists' perceptions of, and interest in, the use of technology to create and enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Nevertheless, for many tourists the vacation is a time to 'unplug' and they use tourism for digital detox. It is related with the Benckendorff, Moscardo, & Murphy (2005) research on high-tech and high-touch travellers distinguishing tourists based on the use of information technologies during travel and everyday life. Therefore, more research should be done on the acceptance of information technologies during the travel journey.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, for many tourists the vacation is a time to 'unplug' and they use tourism for digital detox. It is related with the Benckendorff, Moscardo, & Murphy (2005) research on high-tech and high-touch travellers distinguishing tourists based on the use of information technologies during travel and everyday life. Therefore, more research should be done on the acceptance of information technologies during the travel journey.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, online shopping motivation differs according to the complexity of the website, with variation depending on the Internet skill levels of users (Beldona, Morrison, & O'Leary, 2005). According to the findings of a study conducted in Australia, different types of visitors have different levels of comfort when using technology at tourist attractions (Benckendorff, Moscardo, & Murphy, 2005). Furthermore, Pfaffenberg and Burnett (2007) indicated that the opinions and preference of consumers showed no differences or association in the type of websites they primarily use.…”
Section: Evaluation Of Alternativesmentioning
confidence: 99%
“…Considering this impact, it is unquestioned that the technological developments imply numerous challenges (Benckendorff, Moscardo & Murphy, 2005;Gretzel, Fesenmaier, Formica & O'Leary, 2006) and at the same time, offer great potential for its implementation in the present and future (Wang, Fesenmaier, Werthner & Wöber, 2010). The advent of technology has not only caused radical changes (Cetinkaya, 2009) but has revolutionised the very nature of the tourism industry.…”
Section: Impact Of Icts On the Experiencementioning
confidence: 99%